RESEARCH FRAMEWORK ON THE SUITABLE DEVELOPMENT MODEL AND MECHANISM OF GREEN STTLEMENT IN THE YANGTZE RIVER DELTA - Z. Wang; Y. He; J. Ge (Lowland Technology International, 2004)
By selecting a breakthrough point from the Green Settlement of towns and cities in the Yangtze river delta, which is of great significance to the sustainable development strategy for human sttlement in China, this research tries to integrate the enduring regional "genes" of settlement, to explore the external character and internal law of the basic urban residential unit, and grasp its controlling/adjustment mechanisms. On this base, detailed goals, evaluation systems, space/form modelsand suitable technologies of sustainable development are expected to be established. Thus, the sustainable development strategy for human sttlement in that region can be promoted and serve as a guide for China as a whole.